Investigating the combustion of energetic materials with a boron additive by the method of small-angle X-ray scattering - Pruuél, É. R.; Rubtsov, I. A.; Cheremisin, A. A.; Glotov, Oleg G.; Poryazov, Vasily A.; Surodin, Grigory S.; Kashkarov, A. O.; Studennikov, A. A. (Journal of engineering physics and thermophysics)
The authors have presented results of investigation into the process of combustion of solid specimens consisting of ammonium perchlorate and a binder with boron and aluminum-dodecaboride additives by the method of small-angle x-ray scattering with a high time resolution using high-speed optical photography. An analysis has been made of the particles preserved after the combustion. It has been shown that the procedure of small-angle x-ray scattering permits recording particles of the B and AlB12 additive directly in the combustion wave of the compound.